EDUKASI DAN DEMONSTRASI BALANCE EXERCISE UNTUK MENINGKATKAN KESEIMBANGAN DAN PENGETAHUAN LANSIA DI DUSUN DAWUNG - Fika Putri Rofifah; Helmi Nugraheni; Izah Putri Arisanti; Karunia Febriani HariPutranti; Dewa Sakti Mustika Asa; Salma Lailly Vairasary; Irma Yunita; Asita Rohmah Mutnawasitoh (CV. Denasya Smart Publisher, 2026)
With increasing age, changes occur in the muscles, bones, and joints, leading to a decline in strength, elasticity, and flexibility. These conditions result in reduced balance ability and an increased risk of falls among older adults. Limited knowledge regarding balance disorders and insufficient community-based education remain challenges in preventing fall risks. This community service activity aimed to improve the knowledge and skills of older adults through education and demonstration of balance exercises in Dusun Dawung. The methods included health education on balance disorders, their causes, impacts, and management, followed by direct practice of balance exercises. The results showed an improvement in participants’ understanding, from 61% with low understanding, 29% moderate understanding, and 10% good understanding to 6% low understanding, 13% moderate understanding, and 81% good understanding after the intervention. Participants were also able to perform the exercises independently in a proper and correct manner. This activity was effective in enhancing knowledge and balance ability among older adults and has the potential to reduce the risk of falls.